The Hidden Burden of Dengue and Chikungunya in Chennai, India - Rodríguez-Barraquer, Isabel; Solomon, Sunil S.; Kuganantham, Periaswamy; Srikrishnan, Aylur Kailasom; Vasudevan, Canjeevaram K.; Iqbal, Syed H.; Balakrishnan, Pachamuthu; Solomon, Suniti; Mehta, Shruti H.; Cummings, Derek A. T. (PLOS Neglected Tropical Diseases, 2015)
Author Summary Despite a recent increase in the number of cases, little data exist on the extent of dengue and chikungunya transmission in Indian cities. We conducted a household-based serosurvey conducted in randomly selected spatial locations across the metropolis of Chennai. We tested samples for evidence of previous infection by dengue and chikungunya viruses and used this data to estimate key transmission parameters (force of infection and basic reproductive number) and to explore factors associated with seropositivity. We found that 93% of participants had been exposed to dengue virus, and 44% to chikungunya. We estimate that 23% of the susceptible population gets infected by dengue virus each year, corresponding to approximately 228,000 infections per year. This transmission intensity is almost three times larger than that in traditionally hyperendemic district in Thailand, and suggests an extremely large proportion of asymptomatic/sub-clinical disease, a lack of recognition of the disease and/or under-reporting.